2002
DOI: 10.1103/physrevd.66.032001
|View full text |Cite
|
Sign up to set email alerts
|

Study of the processe+eπ+π

Abstract: Study of the process e + e − → π + π − π 0 in the energy region √ s from 0.98 to 1.38 GeV. The cross section of the process e + e − → π + π − π 0 was measured in the Spherical Neutral Detector experiment at the VEPP-2M collider in the energy region √ s = 980 ÷ 1380 MeV. The measured cross section, together with the e + e − → π + π − π 0 and ωπ + π − cross sections obtained in other experiments, was analyzed in the framework of the generalized vector meson dominance model. It was found that the experimental dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 43 publications
3
56
0
Order By: Relevance
“…III it is clear that the cross section of the process e þ e À ! þ À 0 obtained by BABAR (Aubert et al, 2004b) is consistent with that of SND (Achasov et al, 2002) below ffiffi ffi s p ¼ 1:4 GeV, but is much higher than that at DM2 (Antonelli et al, 1992) above this energy. The energy dependence of the cross section observed by DM2 is also inconsistent with other measurements [see the discussion of this problem by Achasov et al (2002)] and the existence of the rather well-established !ð1420Þ and !ð1650Þ resonances.…”
Section: Some Implications For Theory and Perspectivessupporting
confidence: 88%
See 3 more Smart Citations
“…III it is clear that the cross section of the process e þ e À ! þ À 0 obtained by BABAR (Aubert et al, 2004b) is consistent with that of SND (Achasov et al, 2002) below ffiffi ffi s p ¼ 1:4 GeV, but is much higher than that at DM2 (Antonelli et al, 1992) above this energy. The energy dependence of the cross section observed by DM2 is also inconsistent with other measurements [see the discussion of this problem by Achasov et al (2002)] and the existence of the rather well-established !ð1420Þ and !ð1650Þ resonances.…”
Section: Some Implications For Theory and Perspectivessupporting
confidence: 88%
“…23). The cross section below 1.4 GeV is in agreement with the SND measurement (Achasov et al, 2002), but at higher energies a large deviation from the DM2 results (Antonelli et al, 1992) is observed. The cross section in this region is fitted (see the inset in Fig.…”
Section: A Overviewsupporting
confidence: 82%
See 2 more Smart Citations
“…On the other hand, the bin-to-bin correlated error has been treated as emphasized above for the τ data sets. For reasons already emphasized in [1], we have discarded the e + e − → π + π − π 0 data provided by [46,47].…”
Section: Dealing With the Uncertainties In E + E − Data Samplesmentioning
confidence: 99%